Nominale Adverbiale im Russischen Syntax, Semantik und Informationsstruktur - Szucsich, Luka (Slavistische Beitraege, 2001)
The aim of the present dissertation is to determine the status of nominal adverbials within the grammar of Russian, with a primary focus on syntactic analysis of the adverbials mentioned. It stands both their 'external' structure - i. the embedding position of the adverbials in the sentence structure - as well as the 'internal' structure - i. the category status of nominal adverbials - in the center of the investigation. The analysis of the configurational-syntactic status serves as a starting point to explain the case-relations of 'naked' accusative and instrumental adverbials. However, it is assumed that an explanatory as well as descriptively adequate syntactic analysis is meaningful only if the semantic component of the grammar is taken into account.